Utilization of infrared, Raman spectroscopy for structural analysis of alkali boro-germanate glasses. Issue 1 (31st December 2022) - Taqiullah, S. M.; Alshahrani, Thamraa; Shariq, Mohammad; Hakami, Jabir; Ahmad, Nafis; Alshehri, A. M.; Chaudhary, Anis Ahmad; Khan, M. Shakir; Shinde, Sangram M.; Slimani, Y.; Ansari, Akhalakur Rahman; Siddiqui, Mohd Asim; et al.
Abstract : Melt quenching technique was used to prepare (30-x)Li2 O–xNa2 O–40B2 O3 –30GeO2 glasses (x = 0, 5, 10, 20 & 30 mol %). The room temperature infrared spectra of the powdered glass samples were recorded in the range of 400–2000cm −1 . Raman measurements were performed in the range of 200–2000cm −1 at room temperature. Raman and Infrared spectroscopy was utilized for structural study of this glass system. Specific modes of vibration and peak position were identified from de-convolution of infrared and Raman spectra using Gaussian fitting. Ge–O–Ge bonds' symmetrical stretching vibrations related to 3 members GeO4 rings were allotted to the IR band of 483 cm −1 . The strongest Raman band was allotted to symmetrical stretching vibrations of Ge–O in GeO4 having one non-bridging oxygen with 3 bridging oxygens at 797 cm −1 . The observed Raman and IR spectra of various specimens are utilized here to explain the structural characteristics of current glass.